Development of Computational Physics Practical Instructions: Visualization of the Laplace Equation Phenomenon - Etik Irawati; Hartono Hartono; Sulhadi Sulhadi (Universitas Negeri Semarang, 2025)
Practical instructions for practical activities in computational physics courses have been successfully developed with material on the Laplace equation for temperature distribution. This research aims to produce practical instructions and determine the characteristics, feasibility, and responses of students to practical instructions for computational physics on the Laplace equation. The research design used is development research or R&D (Research and Development) which was modified from Sugiyono. The research was carried out at the Computer Laboratory of PGRI University Semarang with Physics Education study program students as research subjects. The research results show that the computational physics practicum instructions developed have the criteria